The Importance of Ventilator Skilled Nursing Facilities (vSNFs) in the Regional Epidemiology of Carbapenemase-Producing Organisms (CPOs). (4th October 2017) - Lin, Michael Y; Froilan, Mary Carl; Lolans, Karen; Bell, Pamela; Wirth, David; Kemble, Sarah K; Pacilli, Massimo; Black, Stephanie R; Jegede, Olufemi; Runningdeer, Erica; Tang, Angela S; Alu, Chinyere; et al.
Abstract: Background: Patients in long-term acute care hospitals (LTACHs) in the Chicago region have high prevalence of CPO carriage (in previous point prevalence surveys, ~30%). vSNFs care for a similarly ill population and often receive patient transfers from LTACHs. Based on these observations and our results from an earlier study, we hypothesized that vSNFs are reservoirs of CPO-positive patients. Methods: During October 2016–May 2017, all eight vSNFs in the Chicago region were invited to participate in one day point prevalence surveys of residents on their skilled nursing and ventilator wards. Local staff obtained a rectal swab from each resident and collected de-identified patient information assessed at time of survey (age, sex, respiratory support status, length of stay, contact precautions status, facility awareness of resident CPO status). Swabs were processed at a central lab within 6 hours of collection. Overnight growth from MacConkey agar plates was screened, using two commercial multiplex PCR assays (Acuitas ® MDRO gene test, Acuitas Resistome test; OpGen, Gaithersburg, MD) for five carbapenemase gene families (KPC, NDM, VIM, IMP, and OXA-48). Results: Seven of 8 vSNFs and 585 (90%) of 648 eligible residents participated (Table 1). Overall, CPO prevalence was 27% (range, 9% to 37%) and higher in ventilator wards (40%) than skilled wards (10%), P < 0.001. Colonized patients often were not on contact precautions and not recognized by the facility to have CPO carriage (Table 1). The majority of CPO-colonized patients (141/159, 89%) had bla KPC; 31 (5%) of patients identified at 6 vSNFs carried bla VIM. In a multivariable model, respiratory support (mechanical ventilation or tracheostomy collar) and ward type (ventilator ward) were independently associated with increased risk of CPO carriage ( P < 0.001, Table 2). Conclusion: Residents in vSNFs have a high risk for CPO carriage; the risk is highest among those cared for in the ventilator ward, and among those requiring respiratory support (mechanical ventilation or tracheostomy collar). While bla KPC is the most common carbapenemase gene found in the Chicago region, other carbapenemases such as bla VIM may be emerging. When regional public health CPO control efforts target high-risk facilities, vSNFs must be included. Disclosures: M. Y. Lin, OpGen, Inc.: Receipt of donated laboratory services, Research support. Sage, Inc.: receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product. M. K. Hayden, OpGen, Inc.: Receipt of donated laboratory services for project, Research support. Clorox: Grant Investigator, Research support. Molnlycke: Co-I on a different research project for which Molnlycke has contributed product, Conducting studies in healthcare facilities that are receiving contributed product. Sage, Inc.: receipt of contributed product for this project, Conducting studies in healthcare facilities that are receiving contributed product.